Search for exotic states with cc̄ss̄ quark content at Belle and Optimisation of the Photon Monitor for the Belle II pixel detector - Meleshko, Dmytro; Justus Liebig University Giessen (My University, 2026)
This thesis summarises my contribution to two topics: search for quarkonium-like four-quark states in data of the Belle experiment and background monitoring for the pixel detector (PXD). As for the first topic, the Belle experiment was operating from 1999 to 2010 at the KEKB accelerator in Tsukuba, Japan. During the running period, the Belle detector accumulated just under 1ab-1 of collision data, most of which was collected at the centre-of-mass energy of the &#933(4S) resonance, which predominantly decays into a pair of B mesons. The full Belle dataset includes around 1 billion of B meson pairs, making it one of the most valuable samples for rare decay measurements in B meson physics. In 2003 Belle observed the so called X(3872), a state which does not fit the conventional charmonium spectrum and is widely considered as an exotic candidate. Numerous discoveries of unconventional QQ-like candidates followed by Belle and other experiments. Another experiment actively contributing to the quarkonium field -- LHCb at CERN, Switzerland -- reported observation of multiple exotic candidates in the B- → J/ψφK- decay channel in 2017 and 2021. Despite being constrained in the accessible quantum numbers, the analysis reported the observation of seven neutral X candidates with the ccss quark content, many of which had been observed for the first time. Since rediscoveries or refinements of the measurements of these X-states by other experiments are essential to elucidate their nature, a search for ccss candidates in an alternative production mechanism was suggested. In this thesis, we report a search for these and potentially other yet undiscovered exotic states with a ccss quark content in e+e- → Ds+ Ds0*(2317)- and e+e- → Ds+ Ds1(2460)- inclusive processes in the continuum, using the full Belle dataset. The proposed analysis, in comparison with earlier studies, is sensitive to a wider range of quantum numbers and probes a different production mechanism, which was not studied before. The analysis is performed using signal Monte-Carlo simulation, where event reconstruction is verified; generic Monte-Carlo, where complex cross-feed background effects are studied; and data, where a blind search for exotic candidates is carried out. As for the second topic of this thesis, the Belle II experiment is the successor of the Belle experiment, which began recording collision data in 2018. It operates at the upgraded SuperKEKB accelerator, which occupies the same site as its predecessor. The comprehensive on-site facility upgrade included major improvements to the accelerator design, which, among other enhancements, can now reach higher centre-of-mass energies, achieve higher instantaneous luminosity, and operates with a reduced energy asymmetry, enabling a broader physics programme. The upgrade of the Belle II detector involved, to varying extents, improvements to all individual sub-detectors and the development of a new innermost pixel detector, which is designed for reaching the vertex reconstruction resolution in beam direction of 25 μm. These hardware upgrades are aimed to set a new instantaneous luminosity record of up to 6×1035 cm-2s-1 (a factor of 30 higher than the record set by Belle), allowing the experiment to accumulate a total dataset of up to 50 ab-1 over the anticipated lifespan of the Belle II experiment. The increased luminosity, the proximity of the PXD to the interaction point, and the readout via 7.68 million channels impose stringent requirements on the PXD data acquisition system (DAQ). At the design luminosity, the readout rate is expected to exceed 18 Gb/s, which is factor of 10 higher than the combined readout rate of all other sub-detectors. Therefore, a standalone DAQ solution was developed exclusively for the PXD. It includes, in particular, a data acquisition and data truncation system known as Online Selection Nodes (ONSEN), developed in Gießen in collaboration with the IHEP Beijing. A challenge for the PXD is exposure to increased background radiation. Various beam-induced background sources were considered, and their effects had been mitigated or minimised. One such source is the indirect synchrotron radiation (SR), which originates from backscattering off the inner wall of the beryllium beam pipe and primarily affects the inner layer of the PXD. To mitigate this effect, countermeasures were implemented in the beam pipe design during the first long shutdown, which took place from mid-2021 to the end of 2022. As a result of these changes, the SR pattern has changed, necessitating an update to the real-time photon-radiation monitoring tool known as the Photon Monitor, which was accomplished as a part of this thesis. Consequently, this thesis also reports on the update to the Photon Monitor, which accounts for changes of the SR pattern, provides an assessment of background contamination in the previous data taking periods, and delivers a beam optics- and currents-aware prediction of the expected SR contamination for the future runs.
Suche nach exotischen Zuständen mit cc̄ss̄ Quarkinhalt am Belle und Optimierug des Photonmonitors für den Belle II Pixeldetektor
Keywords: Quarkonium; charmonium; PXD; ddc:530